Research Brief on ETI Job Openings Surveys - (:unkn) unknown (My University, 2016)
The Milwaukee job vacancy studies were initiated in 1993 by the University of Wisconsin-Milwaukee Employment and Training Institute at the request of the City of Milwaukee in collaboration with Milwaukee Area Technical College, the Milwaukee Public Schools, and the Private Industry Council of Milwaukee County, and with funding support from the government partners and the Helen Bader Foundation. In 2006 and 2009 the surveys were expanded from the four counties of the Milwaukee metropolitan area to include all seven counties of the Milwaukee Region.
Keywords: job openings; labor market information; job skills mismatch; job spatial mismatch